Pesan Moral Dalam Film “Nikah Muda-Rumah Baru” Karya Turah Pathayana (Analisis Wacana Teun Van Djik) - Fernando Rio Darmawan (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Film is one of the mass media that is effective in conveying a message to a wide audience. In general, films contain a certain moral message based on the theme raised. Nikah Muda – Rumah Baru is a short film directed by Turah Parthayana. This film is about marriage problems at a young age. The study is Karya Turah Parthayana". The purpose of this research is to find out the moral message conveyed in the film Young Marriage – New Home. The research method used is qualitative descriptive, using Teun Van Dijk's theory of discourse analysis model consisting of three aspects, namely text, social cognition, and social context. The moral message in the film is that the decision to marry at a young age requires mental readiness, knowledge, and finances.